1999
DOI: 10.1300/j079v26n01_03
|View full text |Cite
|
Sign up to set email alerts
|

The Predictors of Adolescent Smoking

Abstract: One thousand nine hundred and forty-two junior and senior high school students completed a self-report survey instrument containing measures of cigarette smoking and selected intrapersonal, peer pressure and family functioning variables. Results revealed that peer pressure was significantly associated with smoking behavior across all age × gender cohorts, but that intrapersonal factors were significantly more important to the smoking behavior of 12-13 year-old girls than same-age boys. Within the 14-15 year-ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
15
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 18 publications
2
15
0
Order By: Relevance
“…Risk factors identified in the present study that replicate those found in previous studies of multiple influences include intentions to smoke or susceptibility (Carvajal et al, 2004;Collins & Ellickson, 2004;Pierce, Choi, Gilpin, Farkas, & Merritt, 1996;Sussman et al, 2000), good friend smoking or peer pressure (Barber et al, 1999;Sussman et al, 2000), and low self-efficacy or selfesteem (Barber et al, 1999;Carvajal et al, 2004;Collins & Ellickson, 2004). Risk factors common to other studies that were not found in the present study include hostility or problem behavior (Barber et al, 1999;Collins & Ellickson, 2004), perceived or actual academic performance (Carvajal et al, 2004;Collins & Ellickson, 2004), and addiction concern (Sussman et al, 2000).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Risk factors identified in the present study that replicate those found in previous studies of multiple influences include intentions to smoke or susceptibility (Carvajal et al, 2004;Collins & Ellickson, 2004;Pierce, Choi, Gilpin, Farkas, & Merritt, 1996;Sussman et al, 2000), good friend smoking or peer pressure (Barber et al, 1999;Sussman et al, 2000), and low self-efficacy or selfesteem (Barber et al, 1999;Carvajal et al, 2004;Collins & Ellickson, 2004). Risk factors common to other studies that were not found in the present study include hostility or problem behavior (Barber et al, 1999;Collins & Ellickson, 2004), perceived or actual academic performance (Carvajal et al, 2004;Collins & Ellickson, 2004), and addiction concern (Sussman et al, 2000).…”
Section: Discussionsupporting
confidence: 78%
“…These risk factors include positive attitudes toward smoking (Carvajal, Wiatrek, Evans, Knee, & Nash, 2000;Castrucci, Gerlach, Kaufman, & Orleans, 2002b); peer smoking and peer pressure (e.g., Alexander, Piazza, Mekos, & Valente, 2001;Carvajal et al, 2000;Castrucci, Gerlach, Kaufman, & Orleans, 2002a;Unger et al, 2002;Wills & Cleary, 1997); parental attitude toward smoking and the parent's current smoking status (Carvajal et al, 2004;Castrucci et al, 2002b;Griffin, Botvin, Doyle, Diaz, & Epstein, 1999;Wills & Cleary, 1997); acculturation (Chen, Unger, & Johnson, 1999); problem-behaving friends (SimonsMorton et al, 1999); authoritative parenting and family structure (Griesbach, Amos, & Currie, 2003;Quensel et al, 2002;Simons-Morton et al, 1999); low self-esteem for girls only (Barber, Bolitho, & Bertrand, 1999;Lewis, Harrell, Bradley, & Deng, 2001;Thornton, Douglas, & Houghton, 1999); low socioeconomic status (Lewis et al, 2001); older sibling smoking (Rajan et al, 2003); poor grades (Griffin et al, 1999); perceived stress, anxiety, and coping (Dugan, Lloyd, & Lucas, 1999;Sonntag, Wittchen, Hofler, Kessler, & Stein, 2000); and experimentation with cigarettes (Griffin et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Autonomy may be another internal property that is important to developing resilience because there is a great deal of evidence that 'peer pressure' can encourage smoking. (Barber et al 1999, Vries et al 2003, Tsai et al 2009).…”
Section: Resilience and Smokingmentioning
confidence: 99%
“…For example, Robin and Johnson (1996) reported that perceived peer disapproval of cigarette use was significantly correlated with cigarette use (r = −.38) among a sample of 8 th –12 th graders. Another study that examined friends’ approval of smoking (Barber, Bolitho, & Bertrand, 1999) found some support for the relation between a dichotomous measure of friends’ approval and current smoking in 12- to 17-year-olds.…”
mentioning
confidence: 99%